2013
DOI: 10.1093/infdis/jit384
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae Peptidoglycan-Associated Lipoprotein and Murein Lipoprotein Contribute to Serum Resistance, Antiphagocytosis, and Proinflammatory Cytokine Stimulation

Abstract: Our findings indicate that K. pneumoniae Pal and LppA proteins are important in the maintenance of cell integrity, contribute to virulence, and could be used as attenuated vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…28 Additionally, some OM proteins contribute significantly to the virulence of K. pneumoniae, by conferring protection against host's innate immunity. 29,30 In this study, we demonstrate that YfgL is the major facilitator of K. pneumoniae adherence. Moreover, the YfgL lipoprotein altered integrity of the OM that affects transcriptional expression of the fim operon and production of type-1 fimbriae in K. pneumoniae.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…28 Additionally, some OM proteins contribute significantly to the virulence of K. pneumoniae, by conferring protection against host's innate immunity. 29,30 In this study, we demonstrate that YfgL is the major facilitator of K. pneumoniae adherence. Moreover, the YfgL lipoprotein altered integrity of the OM that affects transcriptional expression of the fim operon and production of type-1 fimbriae in K. pneumoniae.…”
Section: Introductionmentioning
confidence: 55%
“…39,40 Our previous data also demonstrated that capsular polysaccharide (CPS) and OM proteins Pal and LppA, but not OmpA, all play important roles in a PLA K. pneumoniae strain resistance to phagocytosis. 30,41 We showed here that the K. pneumoniae YfgL confers protection against neutrophil phagocytosis, implying that reduced biogenesis of OmpK35/OmpK36 might account for loss of in vivo virulence in the yfgL mutant.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Bacterial lipoproteins are established bacterial virulence factors [1113,24,26,36] that function as inflammatory stimulants in infection and disease progression. Our study is the first to show pro-inflammatory effects of AaPAL, an outer membrane lipoprotein of a major periodontal pathogen, A. actinomycetemcomitans .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a Hemophilus ducrey PAL-deficient mutant strain was less virulent than its parental strain in a human infection model [23], and B. abortus PAL is one of the lipoproteins which causes production of pro-inflammatory cytokines in brucellosis [12]. Klebsiella pneumoniae PAL protects bacterial cells from serum killing, as well as phagocytosis, and is an important virulence factor in a mouse infection model [24]. In addition, strongly immunogenic PAL of Burkholderia cenocepacia [25] facilitates attachment of this opportunistic pathogen to the lung epithelial cells and stimulates IL-8 secretion in cystic fibrosis [26].…”
Section: Introductionmentioning
confidence: 99%